Aristocrazia del sangue e aristocrazia del denaro. L’Euroamerica di Henry James e Frances Hodgson Burnett - Maria Malatesta (Storicamente, 2013)
At the end of the XIXth century and the beginning of the XXth century in USA and Europe a literature arose concerning the comparison between the Old and the New world. Marriage among affluent Americans and ruined European nobles were one of the topics preferred to represent the cultural confrontation between the two societies, their mutual attraction and repulsion. This paper focuses how the complex relationships among the blood aristocracy and the money aristocracy were represented in The American and in The Golden Bowl by Henry James and in The Shuttle, by Frances Hodgson Burnett who put like James the “Euroamerica” at the core of her novels.